2022
DOI: 10.2196/37093
|View full text |Cite
|
Sign up to set email alerts
|

eHealth Interventions for Dutch Cancer Care: Systematic Review Using the Triple Aim Lens

Abstract: Background Globally, the burden of cancer on population health is growing. Recent trends such as increasing survival rates have resulted in a need to adapt cancer care to ensure a good care experience and manageable expenditures. eHealth is a promising way to increase the quality of cancer care and support patients and survivors. Objective The aim of this systematic review was 2-fold. First, we aimed to provide an overview of eHealth interventions and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 127 publications
(188 reference statements)
0
3
0
Order By: Relevance
“…A systematic review describing unmet needs of CRC survivors came to a parallel conclusion, emphasising the requirement for information regarding symptom expectations and management, as well as the continuous support throughout the follow-up [ 26 ]. A recent study conducted three focus groups with the primary objectives to gather insights from CRC survivors to improve care, and explore the potential of e-health technology [ 27 ]. The themes from these focus groups align with our own findings, highlighting the pressing need for information on symptom expectations and management, as well as sustained support during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review describing unmet needs of CRC survivors came to a parallel conclusion, emphasising the requirement for information regarding symptom expectations and management, as well as the continuous support throughout the follow-up [ 26 ]. A recent study conducted three focus groups with the primary objectives to gather insights from CRC survivors to improve care, and explore the potential of e-health technology [ 27 ]. The themes from these focus groups align with our own findings, highlighting the pressing need for information on symptom expectations and management, as well as sustained support during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…For cancer survivors in particular, it has been found that while they use the internet to search for health information, their use of eHealth self-help programmes is not common (Van Uden-Kraan et al, 2019). One reason for this may be that many eHealth interventions are not implemented in everyday practice (Van Deursen et al, 2022). To improve the use of eHealth, the Dutch eHealth Monitor suggests that healthcare providers play an important role in informing patients about eHealth self-help programmes and that healthcare work ows should be designed to facilitate the use of eHealth through blended care (RIVM et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have shown that generally women search more often for health information on the internet [ 57 , 58 ], the studies under review did not provide distinct insights into the intersections of other sociodemographic characteristics in relation to gender and trust in web-based health information [ 56 ]. In addition, other reviews and studies have provided evidence that experience with a certain health condition (eg, cancer [ 4 ]) as well as digital literacy and familiarity in using and navigating web-based tools [ 15 , 59 , 60 ] were associated with more frequent web-based health information seeking and judgmental skills regarding the trustworthiness of different sources.…”
Section: Introductionmentioning
confidence: 99%